A highly dispersed curcumin nano-suspension and a preparation method thereof
By using glycerol premixing and wetting followed by prolonged high-speed stirring and dispersion, combined with a composite colloidal network of xanthan gum and gellan gum, the problems of uneven particle size and poor stability of curcumin nanosuspension were solved, achieving the preparation of highly dispersed and stable curcumin nanosuspension suitable for food and pharmaceutical products.
Patent Information
- Application Number
- CN202511776681.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-28
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2045-11-28
AI Technical Summary
The particle size of curcumin nanosuspension is difficult to control precisely during preparation. The particle size is uneven and the nanoparticles are prone to aggregation, resulting in poor stability and affecting its application in aqueous systems.
A synergistic process of glycerol premixing and wetting combined with long-term high-speed stirring and dispersion, along with the composite colloidal network structure of xanthan gum and gellan gum, is employed to achieve a synergistic effect of thickening and stabilization, thereby controlling particle size and inhibiting particle aggregation.
It achieves uniform particle size and stability of curcumin nanosuspension, ensuring no stratification or precipitation after standing at room temperature for 90 days. It is suitable for food and pharmaceutical products and has good dispersion uniformity and safety.
Smart Images

Figure CN121243066B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of natural pigment technology, specifically to a highly dispersed curcumin nanosuspension and its preparation method. Background Technology
[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
[0003] Curcumin is a chemical compound extracted from the rhizomes of some plants in the ginger family and araceae family. Its molecular formula is C2. 21 H 20 O6, with a relative molecular weight of 368.39, curcumin is a tautomer of a benzene ring-dione structure and an enone structure. Studies have shown that curcumin can not only be used as a natural coloring agent, but also has anti-inflammatory, tissue-regenerating, hangover-relieving, liver-protecting, and anti-cancer effects.
[0004] However, curcumin, as a highly hydrophobic molecule, has poor water solubility and low chemical stability. It is very easy to precipitate and settle in aqueous systems, resulting in poor product uniformity and low bioavailability, which limits its application.
[0005] Nanosuspensions are colloidal dispersions of pure drug submicron particles. Unlike traditional matrix-based nanosystems, nanosuspensions do not require carrier materials. They are stable systems formed by dispersing nanoscale drug particles in water through the stabilizing effects of surfactant charge and steric osmosis. Formulating poorly soluble drugs into nanosuspensions can effectively overcome the problem of low drug bioavailability, increase drug stability, and improve efficacy, allowing them to exert their effects more effectively.
[0006] However, current methods for preparing curcumin nanosuspensions suffer from difficulties in precisely controlling particle size and issues related to particle size uniformity. Furthermore, nanoparticles possess extremely high surface energy, and in order to reduce the system's energy, they strongly tend to aggregate, leading to precipitation and ultimately resulting in poor stability of the curcumin nanosuspension. Summary of the Invention
[0007] To overcome the above problems, the present invention provides a highly dispersed curcumin nanosuspension and its preparation method.
[0008] To achieve the above technical objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a highly dispersed curcumin nanosuspension, the raw materials of which include: Curcumin 7-11 parts, xanthan gum 0.2-0.5 parts, gellan gum 0.1-0.5 parts, glycerin 10-15 parts, and water 150-300 parts.
[0009] A second aspect of the present invention provides a method for preparing the highly dispersed curcumin nanosuspension described in the first aspect, comprising the following steps: (1) Add glycerin to water and mix well to obtain a glycerin aqueous solution; (2) Xanthan gum and gellan gum were added to the glycerol aqueous solution in sequence, and after mixing evenly, curcumin was added. After initial stirring and dispersion, a suspension was obtained; after continuous stirring and dispersion, a highly dispersed curcumin nano suspension was obtained.
[0010] In one or more embodiments, in step (1), the water is ultrapure water.
[0011] In one or more embodiments, in step (1), the temperature of the reaction system is 20~30 ℃.
[0012] In one or more embodiments, the method of mixing evenly in step (1) includes stirring at a speed of 300-600 rpm for 8-15 min.
[0013] In one or more embodiments, in step (2), the temperature of the reaction system is 20~30 ℃.
[0014] In one or more embodiments, in step (2), continuous stirring is maintained during the addition of xanthan gum and gellan gum, and the stirring speed is 300~600 rpm.
[0015] In one or more embodiments, in step (2), during the initial stirring and dispersion process, the stirring speed is 300~600 rpm and the stirring time is 10~120 min.
[0016] In one or more embodiments, during step (2), the stirring speed is 1000~2000 rpm and the stirring time is 12-240 h.
[0017] In one or more embodiments, the curcumin nanoparticles in the curcumin nanosuspension have a particle size of 80-130 nm and an average particle size of 103 nm.
[0018] The beneficial effects of this invention are as follows: (1) The highly dispersed curcumin nanosuspension provided by this invention, through the synergistic process of "glycerol premixing and wetting" and "long-term high-speed stirring and dispersion", can control the particle size of curcumin and solve the problem of uneven particle size. In addition, the composite colloidal network structure formed by xanthan gum and gellan gum in a limited ratio has strong steric hindrance and gel properties, forming a synergistic effect of thickening and stabilization, which can effectively inhibit the Brownian motion and gravitational sedimentation of curcumin particles, improve dispersion uniformity, and make the particle size distribution more uniform. Experiments have confirmed that the highly dispersed curcumin nanosuspension provided by this invention has no stratification and no significant precipitation after standing at room temperature for 90 days, and its stability is far superior to that of samples using only a single colloid or short-term dispersion.
[0019] (2) The raw materials of the highly dispersed curcumin nano suspension provided by the present invention are all food grade or pharmaceutical excipient grade, which are safe and non-toxic. The curcumin nano suspension can be directly used as a raw material and directly added to the end products of various aqueous systems, such as beverages, health products and pharmaceutical products.
[0020] (3) Good process reproducibility: The formula and process parameters provided by this invention are accurate and clear, providing a clear and reliable basis for scaling up from the laboratory to industrial production, and making it easy to achieve large-scale production. Attached Figure Description
[0021] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.
[0022] Figure 1 The images show the initial state and the state of the highly dispersed curcumin nano-suspension prepared in Example 1 after 90 days of storage. Figure 2 The image shown is a low-power transmission microscope image of the highly dispersed curcumin nanosuspension prepared in Example 1; the inset is a particle size distribution diagram. Figure 3 The images show the state of the suspensions prepared in Comparative Examples 1 to 4 after 7 days of storage; where a to d represent Comparative Examples 1, 2, 3, and 4, respectively. Figure 4 This is a schematic diagram illustrating the detection of the relative curcumin content in suspensions prepared with different curcumin addition amounts in Example 2; Figure 5 The relative curcumin content of the highly dispersed curcumin nanosuspension prepared in Example 3 after standing at room temperature for 0-90 days. Detailed Implementation
[0023] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0024] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0025] Currently, the preparation of curcumin nanosuspensions faces challenges such as difficulty in precisely controlling particle size and uneven particle size distribution. Furthermore, nanoparticles possess extremely high surface energy, and in order to reduce the system's energy, they strongly tend to aggregate, leading to precipitation and ultimately resulting in poor stability of the curcumin nanosuspension.
[0026] To achieve the above technical objectives, the present invention adopts the following technical solution: A first typical embodiment of the present invention provides a highly dispersed curcumin nanosuspension, the raw materials of which include: Curcumin 7-11 parts, xanthan gum 0.2-0.5 parts, gellan gum 0.1-0.5 parts, glycerin 10-15 parts, and water 150-300 parts.
[0027] Glycerol and water are mixed in a specified ratio to obtain a glycerol aqueous solution. The glycerol aqueous solution of a specified concentration can improve the hydrophilic environment of curcumin through hydrogen bonding, and will not affect the efficiency of the subsequent dispersion process due to excessive viscosity.
[0028] The precise ratio of curcumin to the composite colloid (xanthan gum and gellan gum) ensures that a sufficient amount of colloid can fully encapsulate curcumin to form nanoparticles. Furthermore, this precise ratio is crucial for achieving optimal suspension and stabilization. Xanthan gum provides high pseudoplasticity and good suspending force, while gellan gum forms a soft and shear-resistant three-dimensional network structure. The combination of these two components creates a strong and stable steric hindrance effect, effectively preventing the sedimentation and aggregation of curcumin.
[0029] A second typical embodiment of the present invention provides a method for preparing the highly dispersed curcumin nanosuspension described in the first aspect, comprising the following steps: (1) Add glycerin to water and mix well to obtain a glycerin aqueous solution; (2) Xanthan gum and gellan gum were added to the glycerol aqueous solution in sequence, and after mixing evenly, curcumin was added. After initial stirring and dispersion, a suspension was obtained; after continuous stirring and dispersion, a curcumin nano suspension was obtained.
[0030] In one or more embodiments, in step (1), the water is ultrapure water.
[0031] In one or more embodiments, in step (1), the temperature of the reaction system is 20~30 ℃.
[0032] In one or more embodiments, in step (2), the temperature of the reaction system is 20~30 ℃.
[0033] Limiting the reaction temperature is crucial for achieving sufficient depolymerization and stable dispersion of curcumin molecules. Subsequent experimental results show that increasing the temperature of the reaction system reduces the stability of the curcumin nanosuspension.
[0034] In one or more embodiments, the method of mixing evenly in step (1) includes stirring at a speed of 300-600 rpm for 8-15 min.
[0035] In one or more embodiments, in step (2), continuous stirring is maintained during the addition of xanthan gum and gellan gum, and the stirring speed is 300-600 rpm.
[0036] In one or more embodiments, in step (2), during the initial stirring and dispersion process, the stirring speed is 300-600 rpm and the stirring time is 10-120 min.
[0037] In one or more embodiments, during step (2), the stirring speed is 1000-2000 rpm and the stirring time is 12-240 h during the continuous stirring and dispersion process. On the one hand, the strong mechanical shear force can effectively break the curcumin aggregates into fine particles, and at the same time, allow the molecular chains of xanthan gum and gellan gum to fully extend and hydrate, forming a dense colloidal network. On the other hand, the dispersion time is the key to achieving physicochemical equilibrium. It ensures the complete hydration of colloidal molecules and the full formation of the network structure; the curcumin fine particles are gradually "fixed" and "encapsulated" in the formed colloidal network, achieving uniform distribution at the microscale; this process is not only "mixing" but also a "structuring" process.
[0038] In one or more embodiments, the curcumin nanoparticles in the highly dispersed curcumin nanosuspension have a particle size of 80-130 nm and an average particle size of 103 nm.
[0039] The highly dispersed curcumin nanosuspension provided by this invention utilizes a synergistic process of "glycerol premixing and wetting" and "long-term high-speed stirring and dispersion" to control the curcumin particle size and solve the problem of uneven particle size. Furthermore, the composite colloidal network structure formed by xanthan gum and gellan gum in a defined ratio exhibits strong steric hindrance and gelling properties, creating a synergistic effect of thickening and stabilization. This effectively inhibits the Brownian motion and gravitational sedimentation of curcumin particles, improving dispersion uniformity. Experiments have shown that the highly dispersed curcumin nanosuspension provided by this invention exhibits no stratification or significant precipitation after standing at room temperature for 90 days, demonstrating stability far superior to samples using only a single colloid or short-term dispersion.
[0040] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.
[0041] In the following examples, the curcumin powder has a purity of ≥95%, the yellow collagen and gellan gum are food grade, and the glycerin is pharmaceutical grade with a purity of 99.5%.
[0042] Example 1 (1) Add 8 g of glycerol to 180 mL of ultrapure water and stir at 500 rpm for 10 min to form a clear and homogeneous glycerol aqueous solution.
[0043] (2) Under continuous stirring (500 rpm), 0.5 g xanthan gum and 0.25 g gellan gum were added slowly and evenly to the glycerol aqueous solution, and stirring was continued for 20 min. Then, curcumin powder was added slowly and evenly, and stirring was continued for 60 min to initially disperse all solid powders in the liquid and form a suspension. Subsequently, the stirring speed was set to 1500 rpm and stirring was continued for 120 h.
[0044] Throughout the dispersion process in steps (1) and (2), the experimental environment temperature must be kept constant at 25 °C, and the operation must be carried out in the dark to prevent curcumin from being degraded by light. At 24 h, 48 h, 72 h and 96 h, the dispersion process can be paused briefly to mix the material adhering to the container wall to ensure the uniformity of the mixture.
[0045] After dispersion, a highly dispersed curcumin nano-suspension was obtained. Figure 1 Here is a physical image of a highly dispersed curcumin nanosuspension, from... Figure 1 As can be seen, the curcumin nano suspension is orange-yellow, has a uniform texture, good fluidity, and no visible particles or precipitates are observed with the naked eye.
[0046] The morphology and size of the samples were characterized by transmission electron microscopy (HT-7700), confirming that the curcumin in the highly dispersed curcumin nanosuspension consisted of curcumin nanoparticles with a particle size of 80–130 nm and an average particle size of 103 nm. Figure 2 ).
[0047] The highly dispersed curcumin nanosuspension was left to stand at room temperature for 90 days, and the results were as follows: Figure 1 As shown, the curcumin nanoparticle suspensions did not exhibit stratification, water separation, or significant precipitation, demonstrating their excellent physical stability. Furthermore, further analysis revealed no significant change in the average particle size of the curcumin nanoparticles.
[0048] Comparative Example 1 Compared with Example 1, this comparative example shortens the continuous stirring time in step (2).
[0049] Under continuous stirring (500 rpm), 0.5 g xanthan gum and 0.25 g gellan gum were added slowly and evenly to the glycerol aqueous solution, and stirring was continued for 20 min. Then, curcumin powder was added slowly and evenly, and stirring was continued for 60 min to initially disperse all solid powders in the liquid, forming a suspension. Subsequently, the stirring speed was set to 1500 rpm, and stirring was continued for 48 h.
[0050] The other methods are exactly the same as in Example 1.
[0051] like Figure 3 As shown in Figure a, the suspension prepared in this comparative example exhibited a slight, visible particle texture in its initial state. After standing at room temperature for 30 days, curcumin precipitated at the bottom of the flask, while the supernatant remained orange-yellow, indicating significantly lower dispersion stability and uniformity compared to the product of Example 1. This demonstrates that prolonged stirring is crucial for achieving stable dispersion of curcumin molecules.
[0052] Further testing revealed that the average particle size of curcumin nanoparticles in the suspension was 1–4 μm.
[0053] Comparative Example 2 Compared with Example 1, the temperature in this comparative example was adjusted to 37 °C throughout the dispersion process.
[0054] The other methods are exactly the same as in Example 1.
[0055] like Figure 3 As shown in Figure b, after dispersion, the initial state of the suspension was thin and highly fluid. After standing at room temperature for 7 days, curcumin precipitate appeared at the bottom of the flask, and the supernatant was light orange-yellow. The dispersion stability and uniformity were significantly lower than those of the product in Example 1. This indicates that maintaining a constant experimental temperature of 20°C to 30°C is crucial for achieving stable dispersion of curcumin molecules.
[0056] Further testing revealed that the average particle size of curcumin nanoparticles in the suspension was 1–4 μm.
[0057] Comparative Example 3 Compared with Example 1, the colloid in this comparative example was adjusted to contain only xanthan gum, without the addition of gellan gum.
[0058] The other methods are exactly the same as in Example 1.
[0059] After dispersion, although the suspension had a certain viscosity, the system showed stratification after standing at room temperature for 7 days. Figure 3 (c) and a soft sediment at the bottom, which can be redispersed with slight shaking, but the long-term stability is not as good as in Example 1. This indicates that the combination of xanthan gum and gellan gum in a limited ratio produces a synergistic effect in improving the long-term structural stability of nanoparticles and preventing phase separation, which is superior to the use of a single colloid.
[0060] Further testing revealed that the average particle size of curcumin nanoparticles in the suspension was 1–4 μm.
[0061] Comparative Example 4 Compared with Example 1, the colloid in this comparative example was adjusted to be gellan gum only, without the addition of xanthan gum.
[0062] The other methods are exactly the same as in Example 1.
[0063] After dispersion, although the suspension had a certain viscosity, the system showed stratification after standing at room temperature for 7 days. Figure 3 (d) and a soft sediment at the bottom, which can be redispersed with slight shaking, but the long-term stability is not as good as in Example 1. This further indicates that the combination of xanthan gum and gellan gum in a limited ratio produces a synergistic effect in improving the long-term structural stability of nanoparticles and preventing phase separation, which is superior to the use of single colloids.
[0064] Further testing revealed that the average particle size of curcumin nanoparticles in the suspension was 1–4 μm.
[0065] Comparative Example 5 Compared with Example 1, this comparative example adjusts the speed and time of continuous stirring.
[0066] Under continuous stirring (500 rpm), 0.5 g xanthan gum and 0.25 g gellan gum were added slowly and evenly to the glycerol aqueous solution, and stirring was continued for 20 min. Then, curcumin powder was added slowly and evenly, and stirring was continued for 60 min to initially disperse all solid powders in the liquid, forming a suspension. Subsequently, the stirring speed was set to 2500 rpm, and stirring was continued for 2 h.
[0067] The other methods are exactly the same as in Example 1.
[0068] After stirring, the suspension exhibited an uneven state with obvious particle aggregation, and stratification and precipitation occurred after standing for 2 hours. This proves that relying solely on short-term high shear force cannot achieve long-term stable dispersion of curcumin in the specific colloidal-glycerol aqueous system of this invention. The key to achieving stable dispersion lies in the process of "combining relatively mild shear force (1000-2000 rpm) with ultra-long duration (12-240 hours)" adopted in this invention.
[0069] Example 2 The amounts of curcumin added were adjusted to: 20 mg / mL, 40 mg / mL, 60 mg / mL, 80 mg / mL, 100 mg / mL, 120 mg / mL, 140 mg / mL, and 160 mg / mL. The amounts of the colloidal compound system, glycerol, and water were the same as in Example 1. The preparation steps were the same as in Example 1.
[0070] Results: Suspensions obtained with different ratios of colloidal / curcumin components all exhibited certain viscosity and stability, and all showed an orange-yellow color. The greater the amount of curcumin added, the deeper the orange-yellow color, and the higher the curcumin content in the final suspension. However, after reaching a certain amount of curcumin, the curcumin content in the final suspension reached saturation. This indicates that under the conditions of a fixed colloidal compound system, glycerol, and water, if a suspension with a higher curcumin content is desired, the amount of curcumin added can be appropriately increased. Figure 4 ).
[0071] Example 3 After curcumin is nano-sized, its specific surface area increases dramatically, and the contact area with adverse environments also increases significantly, which may accelerate degradation. However, the highly dispersed curcumin nano-suspension prepared in this invention maintains a stable curcumin content after standing at room temperature for 90 days. Figure 5 (As shown).
[0072] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a highly dispersed curcumin nanosuspension, characterized in that, The highly dispersed curcumin nano-suspension raw material includes: Curcumin 7-11 parts, xanthan gum 0.2-0.5 parts, gellan gum 0.1-0.5 parts, glycerin 10-15 parts, and water 150-300 parts; The curcumin nanoparticles in the highly dispersed curcumin nanosuspension have a particle size of 80~130 nm and an average particle size of 103 nm. The highly dispersed curcumin nano suspension showed no stratification or significant precipitation after standing at room temperature for 90 days. The preparation method of the highly dispersed curcumin nanosuspension includes the following steps: (1) Add glycerol to water, mix well to obtain an aqueous glycerol solution, and the temperature of the reaction system is 20~30 ℃; (2) Xanthan gum and gellan gum were added to the glycerol aqueous solution in sequence. After mixing evenly, curcumin was added and the mixture was initially stirred and dispersed to obtain a suspension. After continuous stirring and dispersion, a highly dispersed curcumin nano suspension was obtained. During the continuous stirring and dispersion process, the stirring speed was 1500 rpm, the stirring time was 120 h, and the temperature of the reaction system was 20~30 ℃.
2. The preparation method according to claim 1, characterized in that, In step (1), the method for mixing evenly includes stirring at a speed of 300-600 rpm for 8-15 minutes.
3. The preparation method according to claim 1, characterized in that, In step (2), continuous stirring is maintained during the addition of xanthan gum and gellan gum, with a stirring speed of 300-600 rpm.
4. The preparation method according to claim 1, characterized in that, In step (2), during the initial stirring and dispersion process, the stirring speed is 300-600 rpm and the stirring time is 10-120 min.
5. The preparation method according to claim 1, characterized in that, In step (1), the water is ultrapure water.
Citation Information
Patent Citations
Suspended mineral oral liquid and preparation method thereof
CN117694527A
KR20200069870A
